Halal Lifestyle dan Wara' Lifestyle (Studi Kasus Pusat Halal Salman ITB) - Zaidah, Nurul; Solihin, Muhtar; Muliadi, Muliadi (Faculty of Ushuluddin UIN Sunan Gunung Djati Bandung, 2022)
Halal lifestyle is a growing trend today, where the halal lifestyle is a lifestyle that applies everything that is halal or does not conflict with the teachings of Islam. wara', although halal lifestyle is a trend that continues to grow, there are still many who do not understand what a halal lifestyle is, therefore it is necessary for the role of various parties to give special attention so that Muslims get a complete understanding of the concept of halal lifestyle. as done by the Salman ITB Halal Center institution. The purpose of this research is to find out the halal lifestyle and wara' lifestyle, the history of the Salman ITB Halal Center, and the role of the Salman ITB Halal Center in implementing halal lifestyle as a practice of wara' values. The method used is qualitative with the type of case study research using interview, observation and documentation techniques. As for the results of this research, halal lifestyle and wara' lifestyle have harmony so that halal lifestyle is a practice of wara' values. The establishment of the Salman ITB Halal Center was motivated by the issuance of the Halal Product Guarantee Act in 2014, as well as the role of the Salman Halal Center in implementing halal lifestyle which is a practice of wara' values, which can be seen from the vision of the Salman ITB Halal Center which is to become a superior da'wah institution for system services. guarantee of halal products to the public with the strength of halal and professional human resources as well as derivatives of the program organized by the Salman ITB Halal Center.